ANALISIS KINERJA PROYEK “Y”MENGGUNAKAN METODE EARNED VALUE MANAGEMENT (Studi Kasus di PT Asian Sealand Engineering) - Elvi Wahyuni; Bambang Hendrawan (Politeknik Negeri Batam, 2018)
PT Asia Sealand Engineering is a company engaged in offshore industry services. This study aims to profit. (EVM). The EVM concept of the three indicators is the Work Schedule Budget (BCWS), Work Performance Cost Budget (BCWP) and Actual Cost of Work Performance (ACWP). From these indicators are then analyzed to Cost Variance (CV), Cost Performance Index (CPI), Variance Schedule (SV) and Index Performance Schedule (SPI). After these talent indexes can be calculated Estimate at Completion (EAC), Estimate to Complete (ETC) and Time Estimate (TE). The project under study is project